2022
DOI: 10.3389/fbioe.2022.890428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foot-Core Training on Foot-Ankle Kinematics and Running Kinetics in Runners: Secondary Outcomes From a Randomized Controlled Trial

Abstract: This study investigated the effectiveness of an 8-week foot-core exercise training program on foot-ankle kinematics during running and also on running kinetics (impact loads), with particular interest in biomechanical outcomes considered risk factors for running-related injuries in recreational runners. A single-blind, randomized, controlled trial was conducted with 87 recreational runners randomly allocated to either the control (CG) or intervention (IG) group and assessed at baseline and after 8 weeks. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…A total of 28 studies assessed running, 13 involving treadmill running and 15 surface running. Among these studies, ten focused on the effects of different shoes on running biomechanics, [9][10][11][12][13][14][15][16][17][18] three studies examined specific physical interventions, [19][20][21] three studies assessed various gait modifications, [22][23][24] three evaluated foot biomechanics, [25][26][27] two explored the effects of fatigue, 28,29 and two investigated studies the effects of sex. 30,31 Additionally, single studies examined the effects of different surfaces, 32 hamstring flexibility, 33 pertubations, 34 running with different loads, 35 and the differences between transition running and isolated running in triathlon Table 1).…”
Section: Runningmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 28 studies assessed running, 13 involving treadmill running and 15 surface running. Among these studies, ten focused on the effects of different shoes on running biomechanics, [9][10][11][12][13][14][15][16][17][18] three studies examined specific physical interventions, [19][20][21] three studies assessed various gait modifications, [22][23][24] three evaluated foot biomechanics, [25][26][27] two explored the effects of fatigue, 28,29 and two investigated studies the effects of sex. 30,31 Additionally, single studies examined the effects of different surfaces, 32 hamstring flexibility, 33 pertubations, 34 running with different loads, 35 and the differences between transition running and isolated running in triathlon Table 1).…”
Section: Runningmentioning
confidence: 99%
“…Additionally, one study evaluated the inter-individual and intra-individual variability during a squat (Table 4). 70 The median number of participants was 15 [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Squattingmentioning
confidence: 99%
See 1 more Smart Citation
“…An 8-week foot core strengthening program for healthy recreational runners resulted in an increase in the intrinsic anatomical cross-sectional area of the foot muscle, an increase in the propulsive impulse during running ( 11 ), and a significant 2.42-fold reduction in RRI incidence at the 1-year follow-up compared with a placebo stretching program ( 14 ). Matias et al ( 19 ) showed that the foot core exercise program was also capable of changing the foot-ankle kinematic patterns. Individuals who received the intervention showed a more inverted calcaneus and less dorsiflexed midfoot at foot strike, a running pattern at midstance with a less plantar-flexed and more adducted forefoot and a more abducted hallux, and a less dorsiflexed midfoot and less adducted and more dorsiflexed hallux at push-off.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of coordination patterns combines phase dominancy (in-phase or anti-phase) and segmental dominancy (distal or proximal) that highlights differences in the segment motion during the running cycle ( 27 ). Thus, our aim was to reanalyze data from Matias et al ( 19 ) to quantify the coordination pattern of the foot joints of recreational runners who underwent foot core muscle training using the vector coding technique. As the nature of the intervention emphasized the strengthening of the intrinsic muscles of the foot, we hypothesized that the intervention induces positive changes in the coordination patterns that reflect a different interaction of foot-ankle joint pairs during running stance phase.…”
Section: Introductionmentioning
confidence: 99%